1985
DOI: 10.1093/schbul/11.3.427
|View full text |Cite
|
Sign up to set email alerts
|

Negative Symptoms in Schizophrenia: Their Longitudinal Course and Prognostic Importance

Abstract: Negative and positive symptoms were investigated longitudinally in 39 young schizophrenic patients at two followup assessments approximately 2.5 and 5 years after hospital discharge. Negative symptoms, such as flat affect and poverty of speech, which were assessed at the first followup, were found to be effective prognostic signs in schizophrenic patients for predicting later poor role functioning at the second followup. The prognostic importance of negative symptoms was predominantly due to their tendency to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
112
2

Year Published

1987
1987
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(122 citation statements)
references
References 43 publications
8
112
2
Order By: Relevance
“…Recent investigations by Biehl (94), Beiser et al (32) and by Carpenter et al (95) suggest that the presence of the negative symptoms of schizophrenia predicts poor outcome. Recently, however, Husted (57) using findings from the MAP project and other studies (96,97), found no evidence that the presence of negative symptoms at first treatment predicted the level of symptoms at follow-up. While negative symptoms did appear to predict social functioning at follow-up, this effect disappeared when level of premorbid associality and insidiousness of onset were controlled.…”
Section: The Course Of Schizophreniamentioning
confidence: 97%
“…Recent investigations by Biehl (94), Beiser et al (32) and by Carpenter et al (95) suggest that the presence of the negative symptoms of schizophrenia predicts poor outcome. Recently, however, Husted (57) using findings from the MAP project and other studies (96,97), found no evidence that the presence of negative symptoms at first treatment predicted the level of symptoms at follow-up. While negative symptoms did appear to predict social functioning at follow-up, this effect disappeared when level of premorbid associality and insidiousness of onset were controlled.…”
Section: The Course Of Schizophreniamentioning
confidence: 97%
“…The measure of negative symptoms is designed to assess flat affect, poverty of speech, and psychomotor retardation/poverty. Individual items were combined into three subscales reflecting poverty of speech, flat affect, and psychomotor retardation (38,39). Intraclass correlations between raters were 0.96 for the poverty of speech scale, 0.86 for the flat affect scale, and 0.85 for the psychomotor retardation/poverty scale.…”
Section: Followup Assessmentmentioning
confidence: 99%
“…Indeed, negative symptoms have been linked to poor quality of life in individuals with schizophrenia (Hunter and Barry, 2012;Foussias et al, 2014), decreased independent living, functional capacity, and social and role functioning (Pogue-Geile and Harrow, 1985;Bowie et al, 2006;Kring et al, 2013;Fervaha et al, 2014). Moreover, evidence shows that negative symptoms contribute to poor functioning more than positive symptoms of schizophrenia (Rabinowitz et al, 2012).…”
Section: Introductionmentioning
confidence: 99%